2022
DOI: 10.3390/ijms23031510
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drugs as PPARγ Agonists Can Induce PRODH/POX-Dependent Apoptosis in Breast Cancer Cells: New Alternative Pathway in NSAID-Induced Apoptosis

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are considered to be therapeutics in cancer prevention because of their inhibitory effect on cyclooxygenases (COX), which are frequently overexpressed in many types of cancer. However, it was also demonstrated that NSAIDs provoked a proapoptotic effect in COX knocked-out cancer cells. Here, we suggest that this group of drugs may provoke antineoplastic activity through the activation of PPARγ, which induces proline dehydrogenase/proline oxidase (PRODH/POX)-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…However, the stimulation of PRODH/POX by MET in melanoma cells induced ROS-dependent apoptosis, while PRODH/POX knockout abolished the effect ( Oscilowska et al, 2022 ). A similar effect was found in MCF-7 cells treated with non-steroidal anti-inflammatory drugs ( Kazberuk et al, 2022b ). Other studies on MCF-7 and MDA-MB-231 cells highlighted the role of estrogens and estrogen receptors (ERα and ERβ) in PRODH/POX-dependent apoptosis ( Lewoniewska et al, 2021 ).…”
Section: Discussionsupporting
confidence: 74%
“…However, the stimulation of PRODH/POX by MET in melanoma cells induced ROS-dependent apoptosis, while PRODH/POX knockout abolished the effect ( Oscilowska et al, 2022 ). A similar effect was found in MCF-7 cells treated with non-steroidal anti-inflammatory drugs ( Kazberuk et al, 2022b ). Other studies on MCF-7 and MDA-MB-231 cells highlighted the role of estrogens and estrogen receptors (ERα and ERβ) in PRODH/POX-dependent apoptosis ( Lewoniewska et al, 2021 ).…”
Section: Discussionsupporting
confidence: 74%
“…The dysregulated control of inflammation contributes to the initiation, promotion, and metastasis of cancer. Clinical studies have demonstrated that the use of anti-inflammatory drugs displays anti-cancer activity [62][63][64]. The field of tumor immunity is crucial for understanding the dynamics of cancer development, progression, and potential therapeutic interventions (Figure 2).…”
Section: Overview Of Tumor Immunitymentioning
confidence: 99%
“…The simultaneous activation of PPARγ and RXR has been suggested to promote apoptosis, implicating the upregulation of p53 in breast cancer cell lines [ 215 ]. NSAIDs, considered in cancer prevention due to their inhibitory effect on cyclooxygenases (COX), have recently been proposed to exert their antineoplastic activity through the activation of PPARγ, which induces proline dehydrogenase/proline oxidase (PRODH/POX)-dependent apoptosis in breast cancer cells [ 216 ]. In many other studies PPARγ agonists induced apoptosis in bladder cancer [ 217 ], gastric carcinoma [ 133 , 218 ], lung cancer [ 219 ], esophageal adenocarcinoma [ 220 ], pancreatic cancer [ 221 ], hepatocellular carcinoma [ 222 ], neuroblastoma [ 223 ], melanoma [ 141 , 142 ], glioblastoma [ 224 ], leukemia [ 225 ], leiomyoma [ 226 ], mesothelioma [ 153 ], and colon carcinoma [ 227 ].…”
Section: Ppars and Cell Deathmentioning
confidence: 99%